Parental influences on adolescents' physical activity motivation and behavior. - Gaumond, Stéphane. (University of Ottawa (Canada), 2000)
The general purpose of this study was to examine multiple sources of parental influences on adolescents' physical activity motivation and behavior using Self-Determination Theory (Deci & Ryan, 1985, 1991) as the main theoretical framework. More specifically, this study attempted to develop and verify a Model of Parental Influences in the context of physical activity. It was hypothesized that the predicted relationships in the model would be significant and in the expected direction. A questionnaire, composed of several validated scales, that assessed: physical activity motivation, physical activity behavior and perceptions of parental influence, was administered to 829 ninth grade physical education students from the Ottawa, Canada region. Results from a recursive path analysis consisting of two multiple regressions revealed that perceived parental motivation towards physical activity, perceived parental involvement in their physical activities and perceived parental autonomy support in the context of physical activity significantly influenced adolescents' physical activity motivation. Results also revealed that perceived parental expectations with regards to physical activity and adolescents' physical activity motivation were significant predictors of their physical activity behavior. (Abstract shortened by UMI.)
Keywords: Health Sciences, Recreation.